Ti-Al-Mn intermetallic compound and preparation method and application thereof
By adding Zr elements to the Ti-Al-Mn intermetallic compound to form a uniform and dense oxide layer, the problem of insufficient oxidation resistance at high temperature is solved, and excellent high-temperature oxidation resistance and hardness are achieved, which is suitable for high-temperature workpiece applications.
Patent Information
- Application Number
- CN202411706072.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-11
AI Technical Summary
Ti-Al-Mn intermetallic compounds have oxidation problems at high temperatures, resulting in a decrease in their antioxidant capacity, affecting their application in aviation engines, internal combustion engines and other fields.
By adding Zr elements to the Ti-Al-Mn-Zr intermetallic compound, a specific ratio of Ti-Al-Mn-Zr intermetallic compound is prepared to form a uniform and dense oxide layer to improve its oxidation resistance.
The superior oxidation resistance and hardness of Ti-Al-Mn-type intermetallic compounds at high temperatures are achieved, which extends their service life and reduces production costs.
Smart Images

Figure CN119592840A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of intermetallic compounds, and in particular relates to a Ti-Al-Mn series intermetallic compound and a preparation method and application thereof. Background Art
[0002] TiAl-based intermetallic compound is an emerging intermetallic compound structural material with the advantages of low density, high specific strength, and good antioxidant properties. It has great advantages in improving the thrust-to-weight ratio of aerospace engines, improving the fuel combustion efficiency of internal combustion engines, and reducing greenhouse gas emissions. It has important engineering application value in the aerospace industry, weapons industry, and civil industry.
[0003] Ti-Al-Mn intermetallic compounds have become an important development direction of low-cost TiAl alloys in recent years due to their good thermal deformation ability and low raw material cost, and have broad industrial application prospects. However, due to the presence of Mn elements, the high temperature resistance of the alloy has been significantly reduced. Studies have found that during high-temperature oxidation, Mn in Ti-Al-Mn alloys will also undergo selective oxidation, forming granular Mn2O3 distributed in the outermost layer of TiO2, destroying the compactness of the oxide film, thereby seriously deteriorating the high-temperature oxidation resistance of the alloy. From an application perspective, metal materials used in high-temperature applications will inevitably come into contact with air during the service process of aircraft engines, internal combustion engines, etc., and oxidation of the matrix will have a great impact on its performance, and even cause it to fail directly. It can be seen that solving the oxidation problem of such low-cost Ti-Al-Mn intermetallic compounds is a major problem that cannot be ignored in the process of major engineering applications, and it is also a research direction that scientists and researchers must focus on. Summary of the invention
[0004] The purpose of the present invention is to solve the deficiencies of the prior art and provide a Ti-Al-Mn intermetallic compound and a preparation method and application thereof, specifically adopting the following technical solutions:
[0005] On the one hand, the present application provides a Ti-Al-Mn intermetallic compound, whose composition, in atomic percentage, is: Ti 51.0%-53.0%, Al 41.5%-42.5%, Mn 4.5%-5.5%, Zr 1.0%-2.2%, and the remainder is inevitable trace impurities.
[0006] The present application prepares a Ti-Al-Mn intermetallic compound with a specific ratio and adds Zr thereto, so that the compound has excellent oxidation resistance. The addition of the Zr element not only refines the grains of the Ti-Al-Mn intermetallic compound, but also enables a uniform and dense oxide layer to appear on the outer surface of the Ti-Al-Mn intermetallic compound provided by the present application under high temperature conditions. The uniform and dense oxide layer has excellent oxidation resistance and can protect the Ti-Al-Mn intermetallic compound from subsequent oxidation of the material.
[0007] In some preferred implementations, the composition of the Ti-Al-Mn intermetallic compound is, in atomic percentage, 51.0%-51.5% Ti, 42% Al, 5% Mn, 1.5%-2.0% Zr, and the remainder is inevitable trace impurities.
[0008] After a large number of experiments and theoretical studies, the inventors of the present application found that the various components of the Ti-Al-Mn intermetallic compounds provided in the present application have more excellent performance under more specific circumstances, the surface material shedding of the Ti-Al-Mn intermetallic compounds is further reduced, the dense oxide film formed under high temperature conditions is more uniform and reliable, and its hardness is further increased, and it has better stability, reliability and durability under high temperature conditions.
[0009] In some preferred embodiments, the average oxidation rate of the Ti-Al-Mn intermetallic compound in a cyclic oxidation test is less than 0.1 g·m -2 ·h -1 The hardness of Ti-Al-Mn intermetallic compounds is not less than 360 under the HV1.0 hardness test.
[0010] On the other hand, the present application also provides a method for preparing the above-mentioned Ti-Al-Mn intermetallic compound, comprising the following steps:
[0011] Take raw materials providing Ti, Al, Mn, and Zr elements according to atomic percentage;
[0012] The raw materials are smelted to obtain Ti-Al-Mn intermetallic compounds.
[0013] In some embodiments, the method of smelting includes one of vacuum induction melting (VIM), vacuum automatic melting (VAR), and induction skull melting (ISM).
[0014] In some embodiments, the protective atmosphere used in smelting is an inert gas atmosphere, and the pressure of the protective atmosphere is 0.04 MPa-0.1 MPa.
[0015] In some embodiments, the raw materials include titanium sponge, zirconium sponge, high purity aluminum, and purified manganese.
[0016] In some embodiments, the purity of titanium sponge is greater than 99.8%, the purity of zirconium sponge is greater than 99.8%, the purity of high-purity aluminum is greater than 99.8%, and the purity of purified manganese is greater than 99.9%.
[0017] On the one hand, the present application also provides an application of the above-mentioned Ti-Al-Mn intermetallic compound in a high-temperature resistant workpiece, which is one of an engine cylinder liner, an engine bearing, an engine crankshaft, an aircraft engine turbine and an aircraft engine nozzle.
[0018] The beneficial effects of the present application are as follows: the Ti-Al-Mn intermetallic compound provided by the present application has excellent oxidation resistance and hardness under high temperature conditions due to the addition of a specific content of Zr; at the same time, the present application also provides a preparation method of the above-mentioned Ti-Al-Mn intermetallic compound, which has a relatively simple process and can reduce production costs while preparing the above-mentioned Ti-Al-Mn intermetallic compound with excellent performance; in addition, the above-mentioned Ti-Al-Mn intermetallic compound provided by the present application can also be applied to workpieces to ensure that the workpieces maintain stable and reliable performance under high temperature conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The sample surface macroscopic morphology of the sample prepared in Comparative Example 1 after the cyclic oxidation test is shown;
[0020] Figure 2 The figure shows the surface macroscopic morphology of the sample prepared in Comparative Example 2 after the cyclic oxidation test;
[0021] Figure 3 The sample surface macroscopic morphology of the sample prepared in Example 1 after the cyclic oxidation test is shown;
[0022] Figure 4 The sample surface macroscopic morphology of the sample prepared in Example 2 after the cyclic oxidation test is shown;
[0023] Figure 5 Shown is the alloy phase diagram of Ti-Al-Mn intermetallic compounds with Zr addition ranging from 0% to 5%;
[0024] Figure 6 Shown is a microscopic picture of the sample surface after the sample prepared in Comparative Example 1 was subjected to a cyclic oxidation test;
[0025] Figure 7 The microscopic picture of the sample surface after the sample prepared in Example 1 was subjected to the cyclic oxidation test is shown;
[0026] Figure 8 Shown is a microscopic picture of the sample surface after the sample prepared in Example 2 was subjected to a cyclic oxidation test. DETAILED DESCRIPTION
[0027] The following will be combined with the embodiments and drawings to clearly and completely describe the concept and technical effects of the present invention so as to fully understand the purpose, scheme and effect of the present invention. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.
[0028] Example 1
[0029] A Ti-Al-Mn intermetallic compound, whose components in atomic percentage include 52% Ti, 42.0% Al, 5.0% Mn and 1.0% Zr. Its preparation method includes the following steps:
[0030] Weigh 52.0% of sponge titanium, 42.0% of high-purity aluminum, 5.0% of purified manganese and 1.0% of sponge zirconium in atomic weight percentage, add all of the sponge titanium, sponge zirconium, high-purity aluminum and purified manganese into a calcium oxide crucible (melting weight 2.5 kg), and place it in a vacuum induction furnace.
[0031] The vacuum induction furnace is filled with 0.05MPa argon as a protective gas, and electric smelting is performed. After all the sponge titanium, sponge zirconium, high-purity aluminum and purified manganese raw materials in the calcium oxide crucible are melted, the mixture is kept warm and refined for 5 minutes. Then the metal ingot mold is taken for casting. After the casting is completed, the mold is naturally cooled. After complete cooling, Ti-Al-Mn intermetallic compounds are obtained.
[0032] Example 2
[0033] A Ti-Al-Mn intermetallic compound, whose components in atomic percentage include 51% Ti, 42.0% Al, 5.0% Mn and 2.0% Zr. The preparation method thereof comprises the following steps:
[0034] Weigh 51.0% of sponge titanium, 42.0% of high-purity aluminum, 5.0% of purified manganese and 2.0% of sponge zirconium in atomic weight percentage, add all of the sponge titanium, sponge zirconium, high-purity aluminum and purified manganese into a calcium oxide crucible (melting weight 2.5 kg), and place it in a vacuum induction furnace.
[0035] The vacuum induction furnace is filled with 0.05MPa argon as a protective gas, and electric smelting is performed. After all the sponge titanium, sponge zirconium, high-purity aluminum and purified manganese raw materials in the calcium oxide crucible are melted, the mixture is kept warm and refined for 5 minutes. Then the metal ingot mold is taken for casting. After the casting is completed, the mold is naturally cooled. After complete cooling, Ti-Al-Mn intermetallic compounds are obtained.
[0036] Comparative Example 1
[0037] A Ti-Al-Mn intermetallic compound, whose components in atomic percentage include 53% Ti, 42.0% Al, and 5.0% Mn. The preparation method thereof comprises the following steps:
[0038] 53.0% of sponge titanium, 42.0% of high-purity aluminum and 5.0% of purified manganese in terms of atomic weight percentage were weighed, all of which were added into a calcium oxide crucible (melted to 2.5 kg), and placed in a vacuum induction furnace.
[0039] The vacuum induction furnace is filled with 0.05MPa argon as a protective gas, and electric smelting is performed. After all the sponge titanium, sponge zirconium, high-purity aluminum and purified manganese raw materials in the calcium oxide crucible are melted, the mixture is kept warm and refined for 5 minutes. Then the metal ingot mold is taken for casting. After the casting is completed, the mold is naturally cooled. After complete cooling, Ti-Al-Mn intermetallic compounds are obtained.
[0040] Comparative Example 2
[0041] A Ti-Al-Mn intermetallic compound, whose components in atomic percentage include 52.5% Ti, 42.0% Al, 5.0% Mn and 0.5% Zr. Its preparation method includes the following steps:
[0042] Weigh 52.5% of sponge titanium, 42.0% of high-purity aluminum, 5.0% of purified manganese and 0.5% of sponge zirconium in atomic weight percentage, add all of the sponge titanium, sponge zirconium, high-purity aluminum and purified manganese into a calcium oxide crucible (melting weight 2.5 kg), and place it in a vacuum induction furnace.
[0043] The vacuum induction furnace is filled with 0.05MPa argon as a protective gas, and electric smelting is performed. After all the sponge titanium, sponge zirconium, high-purity aluminum and purified manganese raw materials in the calcium oxide crucible are melted, the mixture is kept warm and refined for 5 minutes. Then the metal ingot mold is taken for casting. After the casting is completed, the mold is naturally cooled. After complete cooling, Ti-Al-Mn intermetallic compounds are obtained.
[0044] Comparative Example 3
[0045] A Ti-Al-Mn intermetallic compound, whose components in atomic percentage include 65.0% Ti, 28.0% Al, 5.0% Mn and 2.0% Zr. Its preparation method includes the following steps:
[0046] Weigh 65.0% of sponge titanium, 28.0% of high-purity aluminum, 5.0% of purified manganese and 2.0% of sponge zirconium in atomic weight percentage, add all of the sponge titanium, sponge zirconium, high-purity aluminum and purified manganese into a calcium oxide crucible (melting weight 2.5 kg), and place it in a vacuum induction furnace.
[0047] The vacuum induction furnace is filled with 0.05MPa argon as a protective gas, and electric smelting is performed. After all the sponge titanium, sponge zirconium, high-purity aluminum and purified manganese raw materials in the calcium oxide crucible are melted, the mixture is kept warm and refined for 5 minutes. Then the metal ingot mold is taken for casting. After the casting is completed, the mold is naturally cooled. After complete cooling, Ti-Al-Mn intermetallic compounds are obtained.
[0048] Performance Testing
[0049] High temperature oxidation test and oxidation resistance evaluation: The above embodiments and comparative examples were subjected to cyclic oxidation tests to evaluate their oxidation resistance at 800°C. The specific method is as follows:
[0050] Preparation of experimental samples: The Ti—Al—Mn intermetallic compounds prepared in Example 1, Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 3 were cut into 10 mm×10 mm×5 mm pieces respectively to prepare experimental samples.
[0051] High-temperature oxidation test method: Use a precision balance to weigh each experimental sample and record its original weight; then, under atmospheric conditions, use a sample heating furnace to heat each experimental sample to 800°C, keep warm for one hour and then cool to room temperature, which is one cycle; refer to the Aviation Industry Standard - Oxidation Resistance Test Method for Steel and High-temperature Alloys (HB52580-2000), and perform 100 cycles on each experimental sample. After completing 100 cycles, cool each experimental sample to room temperature, use a precision balance to weigh it, and record the weight after the experiment; use the weight after the experiment minus the original weight to obtain the oxidation weight gain, and the average oxidation rate of each experimental sample can be calculated from the oxidation weight gain and the total time of the oxidation experiment.
[0052] Test results and analysis
[0053] Firstly, the above series of ingot samples were observed by JXA-8530F electron probe (EPMA) under the backscattered electron mode (BSE) mode, and the Figure 1-Figure 4 ,as well as Figure 6-Figure 8 .
[0054] Secondly, after calculating the average oxidation rates of Example 1, Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 3, and classifying the antioxidant grades according to "HB5258-2000", the average oxidation rates and antioxidant grade data of Example 1, Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 3 were sorted out, and the specific data are shown in Table 1.
[0055] Table 1. Antioxidation performance data after 100 cycles at 800℃ / 1h
[0056]
[0057] Combination Figure 1-Figure 4 , and Table 1, which can be analyzed:
[0058] in Figure 1 The sample surface macroscopic morphology of the sample prepared in Comparative Example 1 after the cyclic oxidation test is shown; Figure 2 The figure shows the surface macroscopic morphology of the sample prepared in Comparative Example 2 after the cyclic oxidation test; Figure 3 The sample surface macroscopic morphology of the sample prepared in Example 1 after the cyclic oxidation test is shown; Figure 4 The figure shows the surface macroscopic morphology of the sample prepared in Example 2 after the cyclic oxidation test; Table 1 is a table of the antioxidant performance data of each sample of Example 1, Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 3 after 100 cycles at 800°C / 1h.
[0059] Figure 1 The sample prepared in Comparative Example 1 is shown as a macroscopic morphology of the sample surface after the cyclic oxidation test. The composition thereof includes Ti 53%, Al 42.0%, Mn 5.0% by atomic percentage. Figure 1 It is not difficult to see that obvious black and gray peeling occurs on its surface, and there are a large number of spots that are different from the main color of the sample surface. These spots are oxidation points under high temperature conditions. This is because the sample group in Comparative Example 1 lacks the addition of Zr, resulting in obvious skin peeling and pit-shaped oxidation marks in the 800°C cyclic oxidation experiment. These marks will make the interior of the alloy prone to irregular oxidation, resulting in uneven stress changes in the overall structure of the alloy, and causing serious defects in the overall performance of the alloy. The data in Table 1 also show that after the cyclic oxidation experiment, the average oxidation rate of Comparative Example 1 is relatively high. Although it has antioxidant ability, it is not ideal.
[0060] Figure 2 This is a macroscopic image of the surface of the sample prepared in Comparative Example 2 after the cyclic oxidation test. Its composition, in terms of atomic percentage, includes 52.5% Ti, 42.0% Al, 5.0% Mn, and 0.5% Zr. Figure 2It is not difficult to see that compared with Comparative Example 1, the surface material shedding of Comparative Example 2 is significantly reduced, and the surface color presents a relatively uniform gray distribution over a large range and some black dot marks on the basis of the light-colored main body; these uniformly distributed grays over a large range are relatively slight oxidation marks, indicating that after the 800°C cyclic oxidation experiment, the material has a relatively uniform oxidation situation, indicating that the 0.5% addition of Zr will have a surface oxidation enhancement effect on the Ti-Al-Mn metal, causing a large amount of uniform oxidation on the surface of Comparative Example 2, resulting in a decrease in its anti-oxidation performance. The data in Table 1 also show that the average oxidation rate of Comparative Example 2 is even higher than that of Comparative Example 1. According to analysis, the reason is that due to the low addition of Zr, the surface of the Ti-Al-Mn metal fails to generate a uniform oxide film. Compared with the single-component oxide film generated in Comparative Example 1 without the addition of Zr, when the Zr addition is too low, an oxide film of multiple components is generated on the alloy surface, and gaps are generated between these oxide films, causing the anti-oxidation performance of Comparative Example 2 to decrease instead.
[0061] Figure 3 The sample surface macroscopic morphology of the sample prepared in Example 1 after the cyclic oxidation test is shown. The composition of the sample includes Ti 52%, Al 42.0%, Mn 5.0%, and Zr 1.0% by atomic percentage. Figure 3 It is not difficult to see that the main body of the surface presents a relatively uniform dark brown color. Although some spots with different colors from the main body appear, compared with Comparative Example 1, the number of spots in Example 1 is small, the range is small, the oxidation marks are shallow, and there is no black or gray peeling epidermis in Comparative Example 1; compared with Comparative Example 2, Example 1 does not have a large-scale uniform gray distribution, but the main body of Example 1 presents a relatively uniform dark brown color, and gray and black dot-like oxidation marks appear in some positions; combined with the data of Example 1 in Table 1, the average oxidation rate of Example 1 is greatly improved compared with Comparative Example 1 and Comparative Example 2, indicating that Example 1 has produced a uniform and excellent dark brown oxide film to a large extent, and these oxide films have prevented the oxidation phenomenon from occurring to a large extent, so that the antioxidant performance of Example 1 is significantly improved compared with the Comparative Example and Comparative Example 2.
[0062] Figure 4 The sample surface photograph shown is a sample made in Example 2 after the cyclic oxidation test. Its composition includes Ti 51%, Al 42.0%, Mn 5.0%, and Zr 2.0% by atomic percentage. Figure 4It is not difficult to see that the surface of Example 2 presents a uniform dark brown color over a large range, and the color is uniform, with only a very small number of tiny gray and black dot marks; at the same time, combined with the data of Example 2 in Table 1, the average oxidation rate of Example 2 is the best among Example 1, Example 2, Comparative Example 1, and Comparative Example 2, and the oxidation resistance level of Example 2 reaches complete oxidation resistance. This shows that the Zr content added in Example 2 is just right so that the overall Ti-Al-Mn intermetallic compound can present a uniform and stable surface oxide film in the 800°C cyclic oxidation experiment, so that the outer surface of Example 2 can reach the degree of complete oxidation resistance under the condition of 800°C, and Example 2 has excellent metal surface oxidation resistance.
[0063] From the data in Table 1, it can be found that in Comparative Example 1 and Comparative Example 2, when no Zr is added or the Zr addition amount is too small, the average oxidation rate is significantly higher than that of Example 1 and Example 2, indicating that under the condition of similar Ti, Al, and Mn contents, the addition of Zr has a significant improvement on the average oxidation rate; Comparative Example 3 and Example 2 have the same Zr content added, but the Ti and Al contents are quite different, and the average oxidation rate is also significantly higher than that of Example 1 and Example 2, indicating that under the condition of the same Zr addition amount, the composition ratio of Ti, Al, and Mn has a greater influence on the final average oxidation rate, which will lead to an increase in the average oxidation rate and a decrease in the antioxidant performance.
[0064] In the specific implementation of the present application, the inventors also provide the microstructure and microhardness test results of the alloy ingots of Comparative Example 1, Example 1, and Example 2. The specific data are shown in Table 2.
[0065] Table 2 Microhardness test results of series alloys (HV1.0)
[0066]
[0067] It can be seen from Table 2 that the addition of Zr has a certain refinement effect on the cast solidification structure of the alloy, and the microhardness of the alloy sample surface is also improved to a certain extent.
[0068] In the specific embodiment of the present application, the inventors also used PANDAT to target Ti-Al-Mn intermetallic compounds that can achieve conventional forging deformation. TM (2023) Thermodynamic calculation software was used to perform thermodynamic calculations on the phase diagram of Ti-Al-Mn intermetallic compounds with Zr addition in the range of 0%-5% atomic percentage. The obtained alloy phase diagram of Ti-Al-Mn intermetallic compounds with Zr addition in the range of 0%-5% atomic percentage is shown in Table 2.
[0069] It can be seen from Table 2 that when the Zr addition exceeds 2% by atomic percentage, the alloy begins to precipitate AlZr phase at room temperature. This shows that the maximum solid solubility of the Ti-42Al-5Mn alloy relative to Zr cannot exceed 2% by atomic percentage. Therefore, in order to avoid the precipitation of Zr-containing phases, experimental tests with an atomic percentage of more than 2% are not considered.
[0070] In the specific implementation of the present application, the inventors also provide microscopic images of the sample surfaces of the samples prepared in Comparative Example 1, Example 1 and Example 2 after the cyclic oxidation test; wherein Figure 6 Shown is a microscopic picture of the sample surface after the sample prepared in Comparative Example 1 was subjected to a cyclic oxidation test; Figure 7 The microscopic picture of the sample surface after the sample prepared in Example 1 was subjected to the cyclic oxidation test is shown; Figure 8 Shown is a microscopic picture of the sample surface after the sample prepared in Example 2 was subjected to a cyclic oxidation test.
[0071] From the picture - Figure 8 It can be seen that Ti-42Al-5Mn alloy has obvious coarse grains. With the addition of Zr, these coarse grains disappear, indicating that Zr addition has a certain refinement effect on the alloy cast solidification structure.
[0072] Finally, the above-mentioned Ti-Al-Mn intermetallic compound provided in the present application can be applied to workpieces under high temperature conditions due to its excellent hardness and oxidation resistance, thereby ensuring the performance and reliability of the workpiece.
[0073] Although the description of the present invention has been quite detailed and specifically describes several described embodiments, it is not intended to be limited to any of these details or embodiments or any particular embodiment, but should be regarded as providing a broad possible interpretation of these claims in view of the prior art by reference to the appended claims, thereby effectively covering the intended scope of the present invention. In addition, the above description of the present invention is based on the embodiments foreseeable by the inventor, and its purpose is to provide a useful description, and those non-substantial changes to the present invention that have not yet been foreseen may still represent equivalent changes to the present invention.
Claims
1. A Ti-Al-Mn intermetallic compound, characterized in that: The composition of the Ti-Al-Mn intermetallic compound is calculated in atomic percentage as follows: Ti 51.0%-53.0%, Al 41.5%-42.5%, Mn 4.5%-5.5%, Zr 1.0%-2.2%, and the remainder is inevitable trace impurities.
2. The Ti-Al-Mn intermetallic compound according to claim 1, characterized in that: The composition of the Ti-Al-Mn intermetallic compound is calculated in atomic percentage as follows: Ti 51.0%-51.5%, Al 42%, Mn 5%, Zr 1.5%-2.0%, and the remainder is inevitable trace impurities.
3. A method for preparing a Ti-Al-Mn intermetallic compound as claimed in claim 1 or 2, characterized in that: The preparation method comprises the following steps: Provide raw materials of Ti, Al, Mn and Zr elements according to atomic percentage; The raw materials are smelted to obtain the Ti—Al—Mn based intermetallic compound.
4. The method for preparing a Ti-Al-Mn intermetallic compound according to claim 3, characterized in that: The smelting method includes one of vacuum induction melting (VIM), vacuum automatic melting (VAR) and induction shell melting (ISM).
5. The method for preparing a Ti-Al-Mn intermetallic compound according to claim 3, characterized in that: The protective atmosphere used in the smelting is an inert gas atmosphere.
6. The method for preparing a Ti-Al-Mn intermetallic compound according to claim 5, characterized in that: The pressure of the protective atmosphere is 0.04MPa-0.1MPa.
7. The method for preparing a Ti-Al-Mn intermetallic compound according to claim 3, characterized in that: The raw materials include sponge titanium, sponge zirconium, high-purity aluminum and purified manganese.
8. The method for preparing a Ti-Al-Mn intermetallic compound according to claim 7, characterized in that: The purity of the titanium sponge is greater than 99.8%, the purity of the zirconium sponge is greater than 99.8%, the purity of the high-purity aluminum is greater than 99.8%, and the purity of the purified manganese is greater than 99.9%.
9. Use of the Ti-Al-Mn intermetallic compound according to claim 1 or 2 in high temperature resistant workpieces.
10. The use according to claim 9, characterized in that: The high temperature resistant workpiece is one of an engine cylinder liner, an engine bearing, an engine crankshaft, an aircraft engine turbine and an aircraft engine nozzle.